Optical soliton solutions of the Chen-Lee-Liu equation in the presence of perturbation and the effect of the inter-modal dispersion, self-steepening and nonlinear dispersion - Ozisik, Muslum; Bayram, Mustafa; Secer, Aydin; Cinar, Melih (SPRINGER, 2022)
In this paper, we have investigated the perturbed Chen-Lee-Liu equation which describes the pulse propagation in the optical fibers, under the impact of the inter-modal dispersion, self-steepening and nonlinear dispersion terms. By using the enhanced modified extended tanh expansion method, bright, singular, periodic singular and periodic bright solitons have been obtained and the effects of the coefficients of the inter-modal dispersion, self-steepening and nonlinear dispersion terms on the soliton's dynamics have been examined in each case. In this respect, the review in the article has not been studied and reported before. The computations throughout this paper have been fulfilled by Maple and also the graphical simulations are demonstrated via Matlab.
Keywords: Chen-Lee-Liu model; Modified extended tanh expansion method; DNLSII equation; Optical fiber; Dispersion effect; SCHRODINGER-EQUATION; WAVES; MODULATION; SYSTEMS; FIBERS; Engineering; Physics; Optics